Pan-Islamism and Response to the Collapse of Ottoman Turks in the Dutch East Indies - Prayogi, Arditya (Paramita: Historical Studies Journal, 2023)
This article was written against the backdrop of the position of the Ottoman Turks, which historically had a significant influence on Muslims in the Dutch East Indies. The Muslims of the Dutch East Indies saw that the Ottoman Turks were their political and spiritual representatives. Thus, this article aims to find out the background and response of the Muslims of the Dutch East Indies when the Ottoman Empire was overthrown and replaced with the Republic of Turks. This article used historical research methods with stages in heuristics, criticism/verification, interpretation, and historiography. The data is used as primary data taken from various contemporary mass media reports and secondary data. From the results of the analysis, it is known that the collapse of the Ottoman Turks on 3 March 1924 was responded to by the Muslims of the Dutch East Indies with efforts to revitalize the caliphate through efforts to carry out congresses/meetings, the formation of committees/special agencies and the publication of mass media. The changing image of Turks in the eyes of the Muslim population of the Dutch East Indies eventually contributed to the emergence of new discourses, especially regarding the relationship between Islam and the state in the context of searching for the format of an independent state for Indonesia in the future. This discourse has yet to end in Indonesia and is still experiencing dynamics. Keywords: Pan Islam, Khilafah, Turks, Dutch East Indies, IslamArtikel ini ditulis dengan latar belakang posisi Turki Utsmani yang secara historis memiliki pengaruh signifikan terhadap umat Islam di Hindia Belanda. Umat Islam Hindia Belanda melihat bahwa Turki Usmani adalah perwakilan politik dan spiritual mereka. Maka dari itu, artikel ini bertujuan untuk mengetahui latar belakang dan respon umat Islam Hindia Belanda ketika Kesultanan Utsmaniyah digulingkan dan diganti dengan Republik Turki. Artikel ini menggunakan metode penelitian sejarah dengan tahapan heuristik, kritik/verifikasi, interpretasi, dan historiografi. Data yang digunakan sebagai data primer diambil dari berbagai pemberitaan media massa kontemporer dan data sekunder. Dari hasil analisis diketahui bahwa runtuhnya Turki Utsmani pada tanggal 3 Maret 1924 ditanggapi oleh umat Islam Hindia Belanda dengan upaya merevitalisasi khilafah melalui upaya melakukan kongres/pertemuan, pembentukan panitia/badan khusus dan publikasi media massa. Berubahnya citra orang Turki di mata penduduk Muslim Hindia Belanda akhirnya turut melahirkan wacana baru, khususnya mengenai hubungan Islam dan negara dalam rangka pencarian format negara merdeka bagi Indonesia di Indonesia. masa depan. Wacana ini belum berakhir di Indonesia dan masih mengalami dinamika.Kata kunci: Pan Islam, Khilafah, Turki, Hindia Belanda, Islam